(untitled) (Journal of Production Engineering, 2024)
Measuring cutting forces and shape errors is crucial for understanding and optimizing machining processes. These factors significantly describe the quality, accuracy, and efficiency of manufacturing operations. In this study, the focus is on the turning of X5CrNi18-10, a widely used austenitic stainless steel known for its excellent corrosion resistance and mechanical properties, but challenging machinability due to work-hardening tendencies and high toughness. The study investigates the effects of three key machining parameters—feed rate, depth of cut, and cutting speed—on cutting forces and shape errors, particularly cylindricity. Cutting forces directly impact tool wear, energy consumption, and surface finish, while shape errors reflect the geometric deviations from the intended design, affecting the functionality of machined components. By analyzing these parameters, the study aims to provide insights into the interactions between cutting dynamics and material behavior during turning. It evaluates how variations in feed, depth of cut, and cutting speed influence the magnitude of cutting forces and the resulting geometric precision. These findings contribute to the development of optimized machining strategies, ensuring improved dimensional accuracy, reduced tool wear, and enhanced overall process stability for X5CrNi18-10 and similar materials.